2020
DOI: 10.1111/1471-0528.16168
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 fatty acid supplementation in pregnancy—baseline omega‐3 status and early preterm birth: exploratory analysis of a randomised controlled trial

Abstract: Objective To identify a polyunsaturated fatty acid (PUFA) biomarker able to detect which women with singleton pregnancies are most likely to benefit from omega‐3 supplementation to reduce their risk of early preterm birth. Design Exploratory analysis of a randomised controlled trial. Setting Six Australian hospitals. Population Women with a singleton pregnancy enrolled in the ORIP trial. Methods Using maternal capillary whole blood collected ~14 weeks’ gestation, the fatty acids in total blood lipids were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 21 publications
7
92
1
2
Order By: Relevance
“…The intake of EPA and DHA from the consumption of fish, or fish oils and concentrates (oils containing EPA and DHA in higher concentrations), can confer a range of health benefits, such as lowering blood pressure and reducing the risk for heart disease in adults [ 1 , 2 ]. Specific omega-3 LCPUFAs such as DHA also support the development of the brain and visual system of the fetus during pregnancy [ 3 , 4 , 5 , 6 , 7 , 8 ]. The intake of fish oil can also impart antioxidant effects though the increased expression of antioxidant enzymes, and components in fish oil are associated with antimicrobial effects [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intake of EPA and DHA from the consumption of fish, or fish oils and concentrates (oils containing EPA and DHA in higher concentrations), can confer a range of health benefits, such as lowering blood pressure and reducing the risk for heart disease in adults [ 1 , 2 ]. Specific omega-3 LCPUFAs such as DHA also support the development of the brain and visual system of the fetus during pregnancy [ 3 , 4 , 5 , 6 , 7 , 8 ]. The intake of fish oil can also impart antioxidant effects though the increased expression of antioxidant enzymes, and components in fish oil are associated with antimicrobial effects [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing consumption of EPA and DHA in an untargeted manner (i.e., not guided by level assessments) reduced premature birth before week 34 of pregnancy by 42%, according to a recent Cochrane meta-analysis [16]. Taken together, current data indicate that low levels of EPA and DHA might cause premature birth, providing an argument to determine them before or in pregnancy [11][12][13][14][15][16].…”
Section: Intake Vs Blood Levelsmentioning
confidence: 71%
“…However, post-term induction of labor or caesarean sections were not found to be more frequent in a recent large pertinent meta-analysis, but in one trial some participants reached very high levels [16,40,41]. In contrast, it has recently been reported that some premature births were associated with very high levels of EPA and DHA [13]. Of note, a Mendelian randomization study found little importance for DHA in determining length of gestation, while arachidonic acid seemed to have more relevance [50].…”
Section: Safety and Tolerabilitymentioning
confidence: 92%
See 2 more Smart Citations